PENGARUH CAHAYA AMBIENT TERHADAP EFEKTIVITAS PENYISIHAN RHODAMINE B MENGGUNAKAN MATERIAL KOMPOSIT SPENT BLEACHING EARTH-ZnO - Agus Slamet (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2021)
Adsorption research has been conducted using three types of adsorbents, i.e. SBE, ZnO, and SBE/ZnO for rhodamine B removal. Two research parameters used in this study are dark and light experimental conditions, as well as the initial concentration of rhodamine B solution. The effect of ambient light needs to be studied considering that ZnO is a photocatalyst material. The composite process in this study used SBE activation methods (maceration and acidification), and sol gel method composite synthesis. It has been proven that ambient light affects the performance of SBE/ZnO adsorbent by increasing the adsorption ability by 1.6 mg/g when compared to adsorption in the dark. The adsorption isotherm model analysis corresponds to the Langmuir model with the parameter Qm (maximum adsorption capacity) of SBE/ZnO as 147.05 mg/g.